Apache Hive cookbook : easy, hands-on recipes to help you understand Hive and its integration with frameworks that are used widely in today's big data world /: easy, hands-on recipes to help you understand Hive and its integration with frameworks that are used widely in today's big data world. ([2016]) - Bansal, Hanish; Chauhan, Saurabh; Mehrotra, Shrey
No abstract available